THE PAYMENT OF WAGES FOR OUTSOURCED WORKERS OF PT CAREFASTINDO - Avzurni, Iqbal Samsa; Nuroini, Indi (Acitya Wisesa: Journal of Multidisciplinary Research, 2023)
Outsourcing refers to the use of labor services by contracting out or transferring the duties and responsibilities of work or company activities from the original autonomous parent company to another company as a provider of labor services through the form of a cooperation contract. This research aims to determine whether the implementation of wages for outsourced workers at PT Carefastindo has followed the applicable regulations. The method used in this research is an empirical research study that refers to the results of research in the field. The data used in this research are the implementation and regulations related to the applicable work copyright regulations, evaluations, and interviews with workers at PT Carefastindo. The results indicate that in the implementation of wages for outsourced workers at PT Carefastindo Surabaya, East Java, there is still an implementation of wage payments below the City Minimum Wage. The implementation of wage payments for outsourced workers should fulfill the principle of justice, which refers to proportionality, the provision of salaries, and fulfillment by taking into account achievement and seniority. This wage payment refers to the needs of workers and families from an economic perspective, in accordance with the amount of wages received from the same job as others. Several factors occur in the wages of outsourced workers at PT Carefastindo who are paid below the City Minimum Wage, including the existence of a Cooperation Contract or Work Agreement given to the client of PT Carefastindo.